Criminology and the criminal justice system: a historical and transatlantic introduction - Fijnaut, Cyrille (Intersentia, 2017)
General introduction -- Origin of the present-day criminal justice system -- Restructuring of the criminal justice system during the Enlightenment and the French Period -- Emergence of the scientific study of crime, criminals, and the combatting of crime -- Establishment of criminology in Italy and France -- Development of criminology in German-speaking Europe and the United Kingdom -- Establishment of criminology in the Netherlands and Belgium -- Ideologisation of criminology in the Third Reich and the Soviet Union -- Reception of European criminology in the United States -- Transatlantic integration of criminology -- General conclusion